(untitled) (Scientific journal of the Fergana State University, 2026)
In the current era of rapid digitalization, the need for effective use of information technologies is increasing every day. Modern editing programs not only improve the visual quality of texts but also serve as essential tools for language learning and literacy development. With the growing flow of information and rapid communication, the demand for automatic text editing systems is also rising. This article analyzes the role of automatic editing programs in enhancing literacy, explores their advantages and practical applications, and discusses in detail the impact of these technologies on students’ written language culture.